The nature of thermal radiation from the Universe, Hawking radiation and quasar disks as natural masers (Global Journal of Science Frontier Research, 2024)
The article examines the nature of thermal radiation from the Universe, black holes as a baryonic matter factory and quasar disks as natural masers.
Keywords: baryonic matter; dark matter; black hole; basov's maser